Novel Spinel Li-Cr Nano-Ferrites: Structure, Morphology, and Electrical/Dielectric Properties - Mataev, Mukhametkali; Madiyarova, Altynai; Abdraimova, Moldir; Nurbekova, Marzhan; Seibekova, Karima; Tursyn, Zhanar; Kezdykbayeva, Assel; Ramachandran, Krishnamoorthy; Keskin, Bahadir (MDPI, 2025)
This article reports on the synthesis and physicochemical characterization of a novel complex ferrite material, LiCr3.4Fe1.6O8, prepared via the sol-gel method. X-ray diffraction (XRD) analysis confirmed that the synthesized compound is a single-phase material with a spinel-type structure and cubic symmetry. Raman spectroscopy was employed to investigate the vibrational modes, and the observed peaks corresponding to Fe-O and Cr-O bonds further validated the spinel-like structure of the compound. The microstructure and elemental composition were examined using scanning electron microscopy (SEM). Multiple regions of the LiCr3.4Fe1.6O8 crystals were analyzed, revealing a homogeneous phase and providing detailed insight into the morphology and chemical composition of the surface. The synthesized ferrite particles exhibited relatively large dimensions, with sizes measured at approximately 5, 30, 100, and 200 mu m. The dielectric behavior was studied to assess the material's response to an external electric field, demonstrating its capacity for electric charge polarization. Both capacitance and electrical conductivity were found to increase with rising temperature. Electrophysical measurements were conducted using the LCR-800 system over a temperature range of 293-483 K and at frequencies of 1.5 kHz and 10 kHz. An increase in frequency to 10 kHz resulted in a decrease in the dielectric constant (epsilon) across the entire temperature range.
Keywords: sol-gel method; ferrites; symmetry; X-ray diffraction; pycnometric density; unit cell parameters; scanning electron microscope; MAGNETIC-PROPERTIES; DIELECTRIC-PROPERTIES; COMBUSTION SYNTHESIS; PEROVSKITE; NANOPARTICLES; COMPLEX; SIZE; Biochemistry & Molecular Biology; Chemistry